Influence of pore size of porous titanium fabricated by vacuum diffusion bonding of titanium meshes on cell penetration and bone ingrowth. (15th March 2016) - Chang, Bei; Song, Wen; Han, Tianxiao; Yan, Jun; Li, Fuping; Zhao, Lingzhou; Kou, Hongchao; Zhang, Yumei
Graphical abstract: Abstract: The present work assesses the potential of three-dimensional (3D) porous titanium (pore size of 188–390 μm and porosity of 70%) fabricated by vacuum diffusion bonding of titanium meshes for applications in bone engineering. Rat bone marrow mesenchymal stem cells were used to investigate the proliferation and differentiation of cells on titanium scaffolds with different pore sizes at day 7, day 14 and day 21 based on DNA contents, alkaline phosphatase (ALP) activity, collagen (COL) secretion and osteogenic gene expressions including ALP, COL-1, bone morphogenetic protein-2 (BMP-2), osteopontin (OPN), runt-related transcription factor 2 (RUNX2), using smooth solid titanium plate as reference material. The rabbit models with distal femoral condyles defect were used to investigate the bone ingrowth into the porous titanium. All samples were subjected to Micro-CT and histological analysis after 4 and 12 weeks of healing. A one-way ANOVA followed by Tukey post hoc tests was used to analyze the data. It was found that the differentiation stage of cells on the porous titanium delayed compared with the smooth solid titanium plate and Ti 188 was more inclined to promote cell differentiation at the initial stage (day 14) while cell proliferation (day 1, 4, 7, 10, 14 and 21) and bone ingrowth (4 and 12 weeks) were biased to Ti 313 and Ti 390. The study indicates that the hybrid porous implant design which combines the advantages of different pore sizes may be meaningful and promising for bone defect restoration. Statement of Significance: One of the significant challenges in bone defect restoration is the integration of biomaterials and surrounding bone tissue. Porous titanium may be a promising choice for bone ingrowth and mineralization with appropriate mechanical and biological properties. In this study, based on porous titanium fabricated by vacuum diffusion bonding of titanium meshes, we have evaluated the influence of various pore sizes on rat bone marrow mesenchymal stem cells (rBMMSCs) penetration in vitro and bone ingrowth in vivo . It was interesting that we found the proliferation and differentiation abilities of rBMMSCs, as well as bone ingrowth were related to different pore sizes of such porous scaffolds. The results may provide guidance for porous titanium design for bone defect restoration.